PELATIHAN PENANGANAN DARURAT HIPOGLIKEMIA PADA SISWA DI LINGKUNGAN SMA SWASTA KEMALA BHAYANGKARI I MEDAN - Ariyanti, Ika; Fentiana, Nina; Susyanti, Deni; Olivia, Nina; Wiwin, Wiwin; Monika, Agnes (MAJU : Indonesian Journal of Community Empowerment, 2025)
Hypoglycemia can be influenced by a person's diet and food intake. Teenagers tend to consume foods they like without being balanced with a healthy lifestyle. The purpose of this community service activity is to equip students with basic knowledge and skills in recognizing and dealing with hypoglycemia emergencies. Method: This community service activity includes providing counseling and emergency handling of hypoglycemia. Activities are carried out through lectures, pamphlets and demonstrations of emergency handling of hypoglycemia victims. The results show that training can increase the knowledge of each individual. Before being given counseling, 40% and after being given counseling, 80% had good knowledge. While for the demonstration of emergency handling of hypoglycemia sufferers, 15% could do it but were not perfect and after the demonstration it increased to 85% who could do the handling. Conclusion: Training in emergency handling of hypoglycemia for students is very important to increase awareness, knowledge, and skills in dealing with this condition. With the right training, students can play an active role in maintaining their own health and that of their friends, as well as creating a safer and healthier school environment. This community service activity can have an impact on improving the health of the community